2007
DOI: 10.1111/j.1365-3180.2007.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Some compatible Rhizobium leguminosarum strains in peas decrease infections when parasitised by Orobanche crenata

Abstract: Orobanche crenata (crenate broomrape) produces serious damage to many legume crops and particularly becomes a limiting factor for pea production in the Mediterranean basin. Nodulation effects on pea-broomrape relationships were studied using the commercial pea cultivar Douce de Provence and different Rhizobium strains using pot and Petri dish experiments. First, the benefit of bacterial inoculation on plant growth and efficiency of N incorporation were demonstrated for two isolates, P.SOM and P.1236. These iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 45 publications
9
65
0
Order By: Relevance
“…This suggests that biofilms are much efficient in elicitation of induced systemic resistance in plants thereby, reducing disease incidence. Similar type of increase in defense enzyme activity has been reported by Mabrouk et al [22] and Dutta et al [62] in pea and pigeon pea against fusarial wilt. Osdaghi et al [23] also reported induction of resistance in common bean when bacterized with Rhizobium leguminosarum bv.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This suggests that biofilms are much efficient in elicitation of induced systemic resistance in plants thereby, reducing disease incidence. Similar type of increase in defense enzyme activity has been reported by Mabrouk et al [22] and Dutta et al [62] in pea and pigeon pea against fusarial wilt. Osdaghi et al [23] also reported induction of resistance in common bean when bacterized with Rhizobium leguminosarum bv.…”
Section: Discussionsupporting
confidence: 66%
“…Potential mechanisms include mycoparasitism, competition for nutrients, production of antifungal metabolites like hydrogen cyanide (HCN), antibiotics, siderophore and induction of plant defense mechanisms [18][19][20]. A number of studies showed higher elicitation of enzymes like L-phenylalanine ammonia lyase (PAL), peroxidase (POX) and polyphenol oxidase (PPO) in plants pretreated with rhizobial strains, which play a significant role in induction of systemic resistance against several phytopathogens [21][22][23]. Rhizobia can effectively form biofilm with common soil fungi [6].…”
Section: Introductionmentioning
confidence: 99%
“…foetida (Bouraoui et al, 2012) and the pathosystem pea/O. crenata (Mabrouk et al, 2007). The infection rate reduction was explained by the decrease of the parasite seeds germination stimulation and/or by the presence of necrosis before or after tubercle attachment.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, the nodulated roots displayed high Lox activity related to the overexpression of the lox1 gene. Similarly, the expression of phenylalanine ammonia lyase (PAL) and 6a-hydroxymaackiain 3-O-methyltransferase (Hmm6a) genes were induced early during nodule development, suggesting the central role of the phenylpropanoid/isoflavonoid pathways in the elicited defence (Mabrouk et al, 2007b(Mabrouk et al, , 2007c(Mabrouk et al, , 2010.…”
Section: Biological Controlmentioning
confidence: 99%